YOT Talk: Examining the communicative influences on children’s engagement with youth justice assessment processes - Nuria Lorenzo-Dus (European Journal of Criminology, 2021)
This article presents an evidence-based analysis of the communicative influences on children’s engagement in the Youth Justice System of England and Wales. The multidisciplinary criminologist–linguist ‘YOT Talk’ project utilized Svalberg’s (2009) dimensions of engagement (cognitive, affective, social; augmented by behavioural) to explore the enablers of, and barriers to, children’s engagement with youth justice assessment processes. A tripartite mixed methodology of observation of assessment interviews, questionnaires with children in the Youth Justice System and youth justice practitioners, and focus groups with practitioners was implemented across three Youth Offending Teams in England and Wales. Analyses synergized methods from conversation analysis and corpus linguistics. Findings inform recommendations for refocusing youth justice assessment and staff training on facilitating children’s communicative engagement (that is, enhancing enablers and removing/minimizing barriers). These findings and recommendations challenge asymmetrical (adult-centric) power dynamics during assessment interviews and challenge perceptions of children’s communicative deficits as irreconcilable barriers to effective assessment.